Development of one-step multiplex real-time PCR for the detection of CHV-1, CAdV-2, and CDV - Li, Yifan; Wu, Jingqi; Wang, Chaonan; Jia, Zheng; Yang, Zaixing; Lin, Wei; Ge, Junwei; Zhao, Lili (Frontiers in Veterinary Science, 2025)
Canine Infectious Respiratory Disease Complex (CIRDC) is a highly contagious disease that frequently affects canine populations and has emerged as a global epidemic. It has been reported that CIRDC can have a serious impact on related life. Therefore, the rapid detection and differentiation of common viruses that cause CIRDC are essential. It is generally believed that CIRDC is mainly caused by infection of three pathogens: canine herpesvirus-1 (CHV-1), canine adenovirus-2 (CAdV-2), and canine distemper virus (CDV). In this study, we developed and validated a TaqMan probe-based multiplex real-time PCR method to detect and identify these three viruses simultaneously. We designed specific primers and probes, and optimized the concentrations of each reactant in the system. The method was found to have good sensitivity, specificity and stability, and had a limit of detection of 102 copies/μL, 101 copies/μL and 101 copies/μL for CHV-1, CAdV-2, and CDV, respectively. In addition, co-infection simulation experiments confirmed that the method worked effectively, even if the concentrations of multiple viruses in the sample were close to the limit of detection or the concentrations of different viruses were different. The method was used to detect 122 clinical samples, and the results showed that it was more sensitive and reliable than conventional singleplex PCR. Thus, the method developed in this study is suitable for the clinical monitoring of CIRDC and is of great significance for the prevention and management of respiratory diseases in canine populations.